Northward Propagation of the Intertropical Convergence Zone and Strengthening of Indian Summer Monsoon Rainfall. Issue 23 (29th November 2020) - Hari, Vittal; Villarini, Gabriele; Karmakar, Subhankar; Wilcox, Laura J.; Collins, Mat
Abstract: Since 2002, there has been a clear increase in Indian summer monsoon rainfall (ISMR). We demonstrate that this increase is associated with a change in the dynamics of the Intertropical Convergence Zone (ITCZ). Using a recently released reanalysis product from 1980–2016, we show that the ITCZ has strengthened and propagated northward since 2002. Analysis of the total energy budget reveals an increase in energy divergence and atmospheric diabatic heating, which is consistent with the changes in the ITCZ. Although global aerosol optical depth shows a significant positive trend during 1980–2016, it has declined over many parts of India since 2002. We put forward the hypothesis that this is the driver of the changing characteristics of the ITCZ. Our results suggest that changes in the dynamics of the ITCZ, together with changes in the energy/moisture budget, are responsible for the strengthening of ISMR since 2002, consistent with the emergence of a greenhouse gas‐induced signal. Plain Language Summary: Indian summer monsoon rainfall (ISMR) is a major component of the Asian summer monsoon, providing 80% of the total annual rainfall in India. Even a small deviation of ISMR from normal has a significant effect on the Indian economy. Thus, understanding the dynamics of ISMR is of critical importance. During the latter part of the 20th century, ISMR experienced a significant reduction in its magnitude, with multiple hypotheses proposed to explain this weakening. However, we show that since 2002, there has been a clear increase in the magnitude of ISMR. We propose that this increase in magnitude is associated with the strengthening and northward propagation of the Intertropical Convergence Zone (ITCZ). Further analysis reveals that aerosol optical depth has decreased over many parts of India since 2002. Therefore, we hypothesize that the reduced aerosol emissions have played a significant role in the revival of ISMR since that time. Key Points: The dynamics of the Intertropical Convergence Zone has a significant role in changing the characteristics of the Indian monsoon rainfall Since 2002, the ITCZ has strengthened and propagated northward, thereby increasing the magnitude of the Indian monsoon rainfall The reduced aerosol emissions is the main driver of the changing characteristics of ITCZ, which caused the revival of monsoon rainfall